2014
DOI: 10.1075/target.26.1.04sun
|View full text |Cite
|
Sign up to set email alerts
|

Measuring translation difficulty

Abstract: The Principles of Readability gives a brief introduction to the literacy studies in the U.S. and the research on readability and the readability formulas. Readers' CommentsPlease send all comments and suggestions regarding this document to:William RESEARCH SummaryOver 80 years of research and testing have contributed to the worldwide use in many languages of the readability formulas.They help us improve the text on the level of words and sentences, the first causes of reading difficulty.The principles of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 84 publications
2
37
2
Order By: Relevance
“…Consequently, after reading a TPR study, readers usually wonder how the researchers chose the text(s) to carry out their experiments and how they assessed the level of difficulty or complexity for translation.1 9 1 F 2 O'Brien (2013, p. 117) also notes this lack of adequate operationalization of text selection procedures and claims the use of readability indexes to measure text translatability is "still highly questionable". Other authors have similar criticisms, including Mishra, Bhattacharyya and Carl (2013), Campbell and Hale (2002), Sun and Shreve (2014). However, authors such as Jensen (2009) and Sun and Shreve (2014), for instance, have shown that the use of such indexes in conjunction with other measures can be useful for assessing translation difficulty or complexity and thus for selecting texts for TPR.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, after reading a TPR study, readers usually wonder how the researchers chose the text(s) to carry out their experiments and how they assessed the level of difficulty or complexity for translation.1 9 1 F 2 O'Brien (2013, p. 117) also notes this lack of adequate operationalization of text selection procedures and claims the use of readability indexes to measure text translatability is "still highly questionable". Other authors have similar criticisms, including Mishra, Bhattacharyya and Carl (2013), Campbell and Hale (2002), Sun and Shreve (2014). However, authors such as Jensen (2009) and Sun and Shreve (2014), for instance, have shown that the use of such indexes in conjunction with other measures can be useful for assessing translation difficulty or complexity and thus for selecting texts for TPR.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have similar criticisms, including Mishra, Bhattacharyya and Carl (2013), Campbell and Hale (2002), Sun and Shreve (2014). However, authors such as Jensen (2009) and Sun and Shreve (2014), for instance, have shown that the use of such indexes in conjunction with other measures can be useful for assessing translation difficulty or complexity and thus for selecting texts for TPR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical methods are applied to study difficulties in translation process (Sun & Shreve, 2014), and at editing and post-editing stages, as well (Carl et al, 2011, Kruger, 2012.…”
mentioning
confidence: 99%